THE ROMANIAN SCHOOL OF DENTISTRY. BEGINNINGS, FOUNDING PERSONALITIES - George LUCA; Nicolae MARCU (Romanian Society of Oral Rehabilitation, 2017)
The first department of public dentistry was founded in Jassy, in 1834; the first doctor in this field of study was Iosif Loffler. He had graduated from the University of Pest in 1822 and worked for Doctors' House Trusteeship for a monthly salary of 100 lei. Despite being deprived of many rights, Romanian professionals ranked among the groundbreakers of this medical branch of science in the Austro-Hungarian Empire. The first personality in the field was Dimitrie Nedelcu (1812-1882), descendant of an Aromanian family from Lugoj. After studying Law at the University of Budapest, Nedelcu showed a poignant interest in Medicine, and decided to pursue a career in this field. In 1839 he defended his thesis: Dissertatio inauguralis phisiologico-pathologica de senectute. After that, he specialized in dental art, at Vienna, under the guidance of Georg Carabelli, the founder of this school in the capital city of the Empire. He then returned to Budapest, where he professed medicine until the end of his life, and he turned his efforts towards improving the status of dental art, which had academic appreciation there, as opposed to Bucharest or JassyIn Budapest, dentist Gheorghe Bilascu was Dimitrie Nedelcu's student and asserted himself as one of the most well-known dentists there. He becomes chair of the Dentistry Departmentof the University of Cluj, department founded in 1890 within Faculty of Medicine, thanks to the efforts of dr. Wilhelm Vajna. Deeply convinced of the utility of a mandatory course on dentistry, he suggests it during the faculty meeting held on December 26, 1919 and he asked not only for this, but also for bringing into existence a School of Dentistry in Cluj. Doctor Bilascu argued, with doctor Niculescu, in favour of introducing a Dentistry chair at the Faculty of Medicine in Bucharest, but they never succeeded.